Chronic Failures : Kidneys, Regimes of Care, and the Mexican State - Kierans, Ciara (Book collections on Project MUSE., 2019)
Chronic Failures: Kidneys, Regimes of Care and the Mexican State is about Chronic Kidney Disease (CKD) and the relentless search for renal care lived out in the context of poverty, inequality and uneven welfare arrangements. Based on ethnographic research conducted in the state of Jalisco, this book documents the routes uninsured Mexican patients take in order to access resource intensive biotechnical treatments, that is, different modes of dialysis and organ transplantation. It argues that these routes are normalized, bureaucratically, socially and epidemiologically, and turned into a locus for exploitation and profit. Without a coherent logic of healthcare access, negotiating regimes of renal care has catastrophic consequences for those with the least resources to expend in that effort. In carrying both the costs and the burden of care, the practices of patients without entitlement offer a critical vantage point on the interplay between the state, markets in healthcare and the sick body.